The growth-unemployment relationship in Morocco : Theoretical test and empirical validation: La relation croissance-chômage au Maroc : Essai théorique et validation empirique - FERROUD, Abderrahim; BENJOUID, Zakaria; DABNICHI, Youness (African Scientific Journal, 2021)
We note that today, debates on economic growth and unemployment have taken a primordial place in the development strategies of countries and, above all, are at the heart of economic policies. If the relationship between unemployment and economic growth is correlatively well accepted in the short term; "over the business cycle", this acceptance will not be the same in the long term, "at the structural level". Indeed, long-term analyses of growth and unemployment first developed in separate frameworks highlighting specific determinants (such as R&D for growth or layoff costs for unemployment) and it is only relatively recently, during the 1990s, that a common analytical framework for these two fundamentals of the economy has developed. This paper therefore proposes to test for the Moroccan economy the validity of the theoretical and empirical relationship applied to annual data of real GDP and unemployment covering the period 1986-2019. It is verified the existence of a non-linear relationship between growth and unemployment: cyclical unemployment is more sensitive to variations in GDP (output gap) in recession phases than in expansion phases. One of the simplest and best-known relationships is Okun's law: the stronger the growth, the more jobs the economy generates. Résumé : On remarque qu’aujourd’hui, les débats sur la croissance économique et le chômage ont pris une place primordiale dans les stratégies de développements des pays et surtout sont au cœur des politiques économiques. Si la relation entre le chômage et la croissance économique est corrélativement bien acceptée à court terme ; « au cours du cycle économique », cette acceptation ne sera pas la même à long terme, « au niveau structurel ». Les analyses de long terme de la croissance et du chômage se sont en effet d’abord développées dans des cadres distincts mettant en avant des déterminants spécifiques (comme la R&D pour la croissance ou les coûts de licenciement pour le chômage) et ce n’est que relativement récemment, au cours des années quatre-vingtdix, qu’un cadre d’analyse commun de ces deux fondamentaux de l’économie s’est développé. Cet article propose donc, de tester pour l'économie marocaine la validité de la relation théorique et empirique appliquée à des données annuelles de PIB réel et de chômage couvrant la période 1986-2019. Il est vérifié l’existence d’une relation non linéaire entre la croissance et le chômage : le chômage cyclique est plus sensible aux variations du PIB (output gap) en phases de récession qu’en phases d’expansion. L’une des relations les plus simples et les plus connues est la loi d’Okun : plus la croissance est forte, plus l’économie génère des emplois. Mots clés : Croissance Economique, Chômage, Economie marocaine, Maroc.